Peptide Signaling Pathways Regulate Plant Vascular Development - Yuan, Bingjian; Wang, Huanzhong (Frontiers in Plant Science, 2021)
Plant small peptides, including CLAVATA3/EMBRYO SURROUNDING REGION-RELATED (CLE) and Epidermal Patterning Factor-Like (EPFL) peptides, play pivotal roles in coordinating developmental processes through cell-cell communication. Recent studies have revealed that the phloem-derived CLE peptides, CLE41/44 and CLE42, promote (pro-)cambial cell proliferation and inhibit xylem cell differentiation. The endodermis derived EPFL peptides, EPFL4 and EPFL6, modulate vascular development in the stem. Further, several other peptide ligands CLE9, CLE10, and CLE45 play crucial roles in regulating vascular development in the root. The peptide signaling pathways interact with each other and crosstalk with plant hormone signals. In this mini-review, we summarize the recent advances on peptides function in vascular development, and discuss future perspectives on research of the CLE and EPFL peptides.